KAHOOT: A Game Based Platform for Learning Reading - Muchammad Ichwan Arif; Ahmad Syafii (Journal of English Language Teaching and Islamic Integration, 2018)
This paper reviews Kahoot as a game based learning platform particularly in reading. It provides teachers an opportunity to create game or quizzes and take the scores simultaneously. Moreover, through Kahoot, the students can work hand in hand with their group and compete each other with another group. This situation will enhance their intention to learn and increase their achievement. This research revealed that using Kahoot could increase students reading comprehension.